2017
DOI: 10.1016/j.socscimed.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

How did the Good School Toolkit reduce the risk of past week physical violence from teachers to students? Qualitative findings on pathways of change in schools in Luwero, Uganda

Abstract: Violence against children is a serious violation of children's rights with significant impacts on current and future health and well-being. The Good School Toolkit (GST) is designed to prevent violence against children in primary schools through changing schools' operational cultures. Conducted in the Luwero District in Uganda between 2012 and 2014, findings from previous research indicate that the Toolkit reduced the odds of past week physical violence from school staff (OR = 0.40, 95%CI 0.26–0.64, p < 0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 30 publications
0
34
0
3
Order By: Relevance
“…In terms of exposure to specific Toolkit processes, participation in ‘active groups’, ‘classroom rules’, and Toolkit ‘materials’ were each independently associated with reduced violence, whereas awareness of ‘Tools’ alone was not. However, qualitatively we found that tools such as the ‘wall of fame’ were perceived positively by students and staff suggesting these are important in promoting reward and praise in schools [ 12 ]. In summary, all Toolkit processes seem to be important to bring about change, a finding that supports the idea that multiple and repeated engagement with Toolkit ideas contributes to intervention effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of exposure to specific Toolkit processes, participation in ‘active groups’, ‘classroom rules’, and Toolkit ‘materials’ were each independently associated with reduced violence, whereas awareness of ‘Tools’ alone was not. However, qualitatively we found that tools such as the ‘wall of fame’ were perceived positively by students and staff suggesting these are important in promoting reward and praise in schools [ 12 ]. In summary, all Toolkit processes seem to be important to bring about change, a finding that supports the idea that multiple and repeated engagement with Toolkit ideas contributes to intervention effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Students with mental health difficulties might also have difficulty concentrating and might display behaviours that could be seen as disruptive or challenging to teachers who may not have the tools or techniques to deal with children exhibiting these difficulties [ 31 , 32 ]. This is particularly true in a context with limited teaching resources and large classroom sizes [ 12 , 33 ] and suggests that positive discipline alternatives to physical punishment may not be well applied or may not be sufficient to prevent violence in some circumstances. Such circumstances may challenge teachers who are still transitioning to non-violent approaches to maintain discipline in their school.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Violence in the home and classroom, whether called discipline or abuse, is a widespread problem and has serious consequences. Experiences from Uganda concerning the Good School Toolkit appear to have reduced the risk of violence by teachers on students [50,51], and this may be a useful approach in Sudan and South Sudan. Several studies suggest that parenting programs have the potential to both prevent and reduce the risk of child maltreatment.…”
Section: Childcare Customs and Practicesmentioning
confidence: 99%
“…To fill this gap in the knowledge base, the Good Schools Study was carried out from January 2012 through September 2014 in 42 primary schools in Luwero District, Uganda. The study was designed to assess the impact of the Good School Toolkit on children’s experiences of violence, incorporating four evaluation components: a cluster-randomised controlled trial ( Devries, Knight, et al, 2015 ), a qualitative study ( Kyegombe et al, 2017 ), an economic evaluation ( Greco et al, 2016 ), and a process evaluation ( Knight et al, 2016 ). The trial found the Toolkit to have resulted in a 42% reduction in risk of past-week physical violence from school staff (OR: 0.40; 95%CI: 0.26 to 0.64, p < 0.001) over an 18-month intervention period, as reported by students ( Devries, Knight, et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%